2001
DOI: 10.1590/s1517-74912001000200005
|View full text |Cite
|
Sign up to set email alerts
|

Leucoplasia pilosa oral: aspectos histopatológicos da fase subclínica

Abstract: A leucoplasia pilosa oral (LPO) é uma das manifestações orais mais comuns na AIDS, com valor diagnóstico e prognós-tico. A LPO está relacionada ao Epstein-Barr vírus (EBV), com características clínicas e histopatológicas definidas. Já existem relatos de uma fase subclínica da LPO, porém sem caracterização histopatológica. O presente trabalho teve por objetivo descrever os aspectos histopatológicos desta fase, bem como realizar uma análise comparativa entre a LPO subclínica e clínica, com a finalidade de verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
6
0
4
Order By: Relevance
“…OHL diagnosis is now based on cell morphology (histopathology and cytopathology), associated or not with EBV demonstration (immunohistochemistry, in situ hybridization, polymerase chain reaction or electronic microscopy). Many studies have demonstrated cytopathology specificity 6,7,11 . In HIV children, the accomplishment of a biopsy represents difficulty comparable to that involved in its accomplishment in adults, amplified by the delicate approach involved.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…OHL diagnosis is now based on cell morphology (histopathology and cytopathology), associated or not with EBV demonstration (immunohistochemistry, in situ hybridization, polymerase chain reaction or electronic microscopy). Many studies have demonstrated cytopathology specificity 6,7,11 . In HIV children, the accomplishment of a biopsy represents difficulty comparable to that involved in its accomplishment in adults, amplified by the delicate approach involved.…”
Section: Discussionmentioning
confidence: 99%
“…Oral hairy leukoplakia (OHL) was first described in 1984 and was considered to be an early marker of HIV infection in adults. It is associated with the Epstein-Barr virus (EBV), a double-stranded DNA virus which belongs to the human herpesvirus group 7,14 . Clinically, OHL manifests itself as a flat, corrugated or hairy nonremovable asymptomatic white lesion, most commonly on the lateral border and/ or ventral surface of the tongue 10 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations